High dynamic range whole-field turbulence measurements in impinging synthetic jets for heat transfer applications - PERSOONS, TIM; MURRAY, DARINA; FARRELLY, RAYHANN (My University, 2010)
For applications requiring high local heat transfer rates, recent research has shown that impinging synthetic jets perform comparably to continuous jets, yet without needing external mass flow input. In spite of recent attention, the understanding of synthetic jet heat transfer mechanisms remains incomplete. The heat transfer performance strongly depends on flow conditions (e.g. Reynolds number, stroke length), geometric parameters (e.g. jet-to-surface distance, orifice shape). Furthermore, vortex trains of adjacent synthetic jets can interact to establish flow vectoring and significant heat transfer enhancements. Most parameters (stroke length, jet-to-surface distance, phase lag between adjacent jets) have a highly non-monotonic influence on heat transfer performance. Accurate whole-field turbulence and flow measurements are crucial to understanding the heat transfer mechanisms, thereby enabling optimal design of synthetic jet based heat transfer applications. Particle image velocimetry (PIV) is the preferred technique, using state of the art adaptive multi-grid correlation with window deformation. However, the dynamic range of the conventional PIV approach is too limited to accurately resolve both high velocities near the orifice and low turbulence intensities in the wall jet region. This paper applies a simple and robust technique based on multiple pulse separation (MPS) double-frame imaging. For the impinging jet flows under investigation, the MPS-PIV technique increases the dynamic velocity range by more than an order of magnitude compared to a conventional multi-grid PIV measurement. The technique is validated on a steady jet test case against LDV measurements. The paper describes some advances in synthetic jet heat transfer by comparing turbulence intensity distributions and local heat transfer rates. In this configuration with a wide velocity range, MPS PIV enables whole-field measurements without sacrificing resolution in the low velocity regions (i.e. wall jet and entrainment regions) which are crucial to understand the governing heat transfer mechanisms.
15th Int Symp on Applications of Laser Techniques to Fluid Mechanics
PUBLISHED
Lisbon, Portugal
Keywords: Mechanical Engineering; turbulence PIV; synthetic jets; Smart & Sustainable Planet; Telecommunications